Participation of First-Degree Relatives of Women with Breast Cancer in Screening Programs - Kadriye Aldemir; Aysel Gürkan; Feride Taskın Yılmaz; Gülbahtiyar Demirel (Zanjan University of Medical Sciences and Health Services, 2019)
Background: First-degree female relatives of the patients with breast cancer  have a higher risk of breast cancer than the general population does due to shared genetic factors and environmental and lifestyle similarities. Objectives: This study was conducted to determine the participation status of first-degree relatives of women with breast cancer in screening programs. Methods: This descriptive and cross-sectional study was conducted from May 2 to September 30, 2019, in the oncology unit of a university hospital in Turkey. All women who were first-degree relatives of registered patients at the specified time were considered without going through sample selection. Accordingly, 281 first-degree relatives of 135 breast cancer patients were included in the study. The data were collected by means of face-to-face interviews, the individual identification form created by the researchers in line with the literature, and the breast cancer screening program participation form. The data obtained from the study were evaluated using numbers, percentage distribution, arithmetic mean, and chi square test in the SPSS 23 statistical program. Results: In this study, it was found that only 63.3% of women knew breast self-examination, and only 37.4%of those women do it regularly. Morover 34.9% of women stated that they had clinical breast examinations before, and 24.6% had mammography before. It was found that women with secondary education or higher and benign breast disease had higher participation rates in all screening programs, and women over 40 years of age had higher rates of clinical breast examination and mammography (p<0.05). Conclusion: We concluded that women with first-degree relatives who have breast cancer do not adequately participate in the breast cancer screening program. We recommned information trainings be organized to raise awareness of women at risk group in terms of screening